Formation and decay of resonance state in 9Be and 9B nuclei. Microscopic three-cluster model investigations (Physical Sciences and Technology, 2017)
We study nature of the low-lying resonance states in mirror nuclei 9Be and 9B. Investigations are performed within a three-cluster model. The model make uses of the hyperspherical harmonics, which provide convenient description of three-cluster continuum. Much attention is paid to the controversial 1/2+ resonance states in both nuclei. We study effects of Coulomb interaction on energy and width of three-cluster resonances in the mirror nuclei 9Be and 9B. We look for the Hoyle-analogue states which allows for alternative way of 9Be and 9B synthesis in a triple collision of clusters.
Keywords: Microscopic model; triple collision; resonance state